(untitled) (Global Journal of Human-Social Science, 2025)
The degree to which students understand the subjects taught in schools largely depends on the educational environment In resource-poor regions particularly in resource-poor developing countries this environment is often inadequate severely hindering learning outcomes Here the mixed-methods approach was used to assess the degree to which students understand chemical formulas and equations taught in Senior Secondary Schools SSS in Sierra Leone A total of 158 SSS II and SSS III students across 6 schools in Bo City were randomly selected Bo City is the regional headquarter of the Southern Region of Sierra Leone Diagnostic pre-test results showed an alarming deficiency among students regarding the level of knowledge of foundational chemistry Only 3 6 of the students correctly formulated Lithium Trioxosulphate IV and only another 7 3 accurately balanced the sodium-chlorine reaction equation Qualitative analysis further showed a widespread misconception of the IUPAC nomenclature 63 29 and polyatomic ion valencies 88 3 Additionally 77 of the students failed to correctly identify NaCl compound and some 53 7 properly balanced the related chemical equations